MEMBANGUN PENDIDIKAN ANTIKORUPSI DI SEKOLAH DASAR (Jurnal Pendidikan Dasar, 2019)
Corruption almost did in all of side government start from underling to elite. It is did massively by scandalist used various manner and type wich very complex without see the status. Therefore, need the effort for extirpate it, especially for elementary school students did prevently. It is effort can did with build anticorruption education in elementary school. This is have purpose for give knowledge, kind, and the manner prevent various corruption form. Anticorruption education is the effort to do awarely for teach anticorruption education. Not only the teacher have obligation for teach it, but also headmaster as a leader in elementary school have important role to build anticorruption education. Curriculum of anticorruption education emphasized on all of lessons such as social studies, natural science, and language. Whereas for give various fasilities the style of student study (visual, auditory, and cinestetic), then teacher could use various models instruction so the activities learning not monotonous and students not bored quickly. The assessment could used on anticorruption education is authentic assessment.